Grandiose narcissism, unfounded beliefs, and behavioral reactions during the COVID-19 pandemic - Zemojtel-Piotrowska, M. (2024)
A theoretical perspective on grandiose narcissism suggests four forms of it (sanctity, admiration, heroism, rivalry) and states that these forms conduce to different ways of thinking and acting. Guided by this perspective, we examined in a multinational and multicultural study (61 countries; N = 15,039) how narcissism forms are linked to cognitions and behaviors prompted by the COVID-19 pandemic. As expected, differences in cognitions and behaviors across narcissism forms emerged. For example, higher narcissistic rivalry predicted lower likelihood of enactment of COVID-19 prevention behaviors, but higher narcissistic sanctity predicted higher likelihood of enactment of COVID-19 prevention behaviors. Further, whereas the heroism, admiration, and rivalry narcissism forms acted in a typically antisocial manner, with high narcissism predicting greater endorsement of unfounded health beliefs, the sanctity form acted in a prosocial manner, with higher narcissism being linked to lower endorsement of unfounded COVID-19 health beliefs. Thus, the findings (a) support the idea of four narcissism forms acting differently, and (b) show that these differences reflect a double-edged sword, sometimes linking to an anti-social orientation, and sometimes linking to a pro-social orientation.